Microsurgical Reconstruction for Head and Neck Cancer in Elderly Patients - Spyropoulou, Georgia-Alexandra; Jeng, Seng-Feng; Hsieh, Ching-Hua; Tsimponis, Antonis; Shih, Hsian-Shun (Journal of Reconstructive Microsurgery, 2014)
The purpose of this study is to review our group of elderly patients and examine whether microsurgical reconstruction is safe to perform in these cases. From October 2006 to October 2009, 747 patients with head and neck cancer who underwent free flap reconstruction were divided into two groups: patients younger than 70 years (n = 714) and patients older than 70 years (n = 33). The two groups of patients were compared regarding medical comorbidities, medical/surgical complications, smoke, and alcohol consumption and outcomes. Two deaths occurred in the “elderly” (6% mortality rate) group of patients and two deaths in the “young” group of patients (0.28% mortality rate) in the immediate postoperative period (15 days postoperatively). Thus, mortality rate had a significant difference (p = 0.011) between these two groups. There was no significant difference in morbidity between these two groups of patients regarding the rate of medical complications, surgical complications, flap failure, and reexploration during our 3-month follow-up period. Mortality risk is higher in the elderly group of patients. However, there is no significant difference regarding the free flap success rate between these two groups. Thorough preoperative evaluation and preparation are critical to achieve a favorable outcome in elderly patients.
Keywords: free flap transfer; head and neck reconstruction; elderly patient